Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
18-6 July 31, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Extreme inner end. Nordenskjold Glacier. Photo taken looking west from motor boat.